Ethnoveterinary research and development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Ethnoveterinary research and development edited by Constance McCorkle, Evelyn Mathias and Tjaart W Schillhorn van Veen 1996 338pp ISBN I 85339 326 6